2016
DOI: 10.1038/srep26823
|View full text |Cite
|
Sign up to set email alerts
|

Continuity of Monolayer-Bilayer Junctions for Localization of Lipid Raft Microdomains in Model Membranes

Abstract: We show that the selective localization of cholesterol-rich domains and associated ganglioside receptors prefer to occur in the monolayer across continuous monolayer-bilayer junctions (MBJs) in supported lipid membranes. For the MBJs, glass substrates were patterned with poly(dimethylsiloxane) (PDMS) oligomers by thermally-assisted contact printing, leaving behind 3 nm-thick PDMS patterns. The hydrophobicity of the transferred PDMS patterns was precisely tuned by the stamping temperature. Lipid monolayers were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 52 publications
(94 reference statements)
0
14
0
Order By: Relevance
“…After that, the prepared vesicle solutions were extruded 20 times through 50-nm-diameter pores (PC membrane, Avanti Polar Lipids Inc., USA) to prepare uniformly sized, small unilamellar vesicles (SUV; 0.1 mg mL −1 ). The 50-nm-diameter SUVs spontaneously rupture on a hydrophilic SiO 2 surface and form a uniform and defect-free SLB patch on the SiO 2 surface of the EG 33 , 34 . For negative controls for biotin–avidin binding, Cholera toxin subunit B proteins (CTxB, Invitrogen, USA, MW= 12 kDa) specifically bound to ganglioside GM1 lipids were used.…”
Section: Methodsmentioning
confidence: 99%
“…After that, the prepared vesicle solutions were extruded 20 times through 50-nm-diameter pores (PC membrane, Avanti Polar Lipids Inc., USA) to prepare uniformly sized, small unilamellar vesicles (SUV; 0.1 mg mL −1 ). The 50-nm-diameter SUVs spontaneously rupture on a hydrophilic SiO 2 surface and form a uniform and defect-free SLB patch on the SiO 2 surface of the EG 33 , 34 . For negative controls for biotin–avidin binding, Cholera toxin subunit B proteins (CTxB, Invitrogen, USA, MW= 12 kDa) specifically bound to ganglioside GM1 lipids were used.…”
Section: Methodsmentioning
confidence: 99%
“…After that, the prepared vesicle solutions were extruded 20 times through 50-nm-diameter pores (PC membrane, Avanti Polar Lipids Inc., USA) to prepare uniformly sized, small unilamellar vesicles (SUV; 0.1 mg/mL). The 50-nm-diameter SUVs spontaneously rupture on a hydrophilic SiO 2 surface and form a uniform and defect-free SLB patch on the SiO 2 surface of the EG 42,43 . For negative controls for biotin-avidin binding, Cholera toxin subunit B proteins (CTxB, Invitrogen, USA) speci cally bound to ganglioside GM1 lipids were used.…”
Section: Methodsmentioning
confidence: 99%
“…Membranes containing SPM, CHOL, and ganglioside GM1 prepared on the S-PDMS regions were found to display a selective accumulation of l o domains at the monolayer regions (Fig. 5c) 20 . Recently, we reported that the heterogeneous SLB patch in different lipid compositions resulted in scheduled l o domain formation, using the methods described in Fig.…”
Section: Raft-assisted Membrane Bendingmentioning
confidence: 95%
“…1e). The appropriate surface hydrophobicity (= interfacial energy) for the reconstitution of lipid monolayers in vitro is explained in Ryu et al 20 . In the case of the lipid bilayer, silicabased surfaces (e.g., glass, silicon wafer, and quartz wafer) were piranha cleaned for rendering the hydroxyl (-OH) group on the outermost surface.…”
Section: Supported Lipid Bilayer (Slb)mentioning
confidence: 99%
See 1 more Smart Citation